SAT-740 Plasma Glucocorticoids and Mineralocorticoids Are Associated to Metabolic Syndrome Features in Women - Ostinelli, Giada (J Endocr Soc, 2020)
Background: Excess visceral adipose tissue accumulation on anatomical structures such as the greater omentum and mesentery are strong predictors of obesity-associated comorbidities (1). High glucocorticoid levels have been associated with body fat distribution and preferential visceral fat accumulation as well as features of the metabolic syndrome (MetS) (2). These effects are thought to be mediated by the glucocorticoid receptor, a nuclear receptor showing affinity for both glucocorticoids and mineralocorticoids. In this study, we examined plasma concentrations of glucocorticoids and mineralocorticoids in women with or without the MetS. In addition, we assessed the ability of these steroids to predict fat accumulation and features of the MetS. Methods: In a sample of 49 women (age 47 ± 4.99 years; BMI 26.4 ± 4.70 kg/m(2)), plasma concentrations of cortisol, 11-deoxycortisol, cortisone, aldosterone, corticosterone and 11-deoxycorticosterone were analyzed by electrospray ionization-liquid chromatography-tandem mass spectroscopy (ESI-LC-MS/MS). Metabolic parameters were assessed to establish the presence of the MetS using NCEP-III criteria. Subcutaneous and visceral adipocyte cell size was measured by histomorphometry. Results: We found HDL-triglycerides to be positively associated with levels of 11-deoxycorticosterone, 11-deoxycortisol, corticosterone, cortisone and cortisol (p<0.05 for all). 11-deoxycorticosterone concentration was also negatively associated with waist circumference (-0.294, p<0.05), LDL-cholesterol and LDL-triglyceride content (-0.264 and -0.362, p<0.05) whereas cortisone level was positively associated with fasting glucose (0.3, p<0.05). Our model including mineralocorticoids predicted systolic blood pressure (R(2)=0.303), while the one including glucocorticoids predicted HDL-cholesterol (R(2)=0.495). In addition, as expected, we found that women with the MetS were characterized by significantly higher percentage body fat and displayed subcutaneous and visceral adipocyte hypertrophy (p<0.05). Interestingly, women with the MetS also showed a trend for lower plasma cortisol concentrations (p=0.07). Conclusion: Our data suggest that glucocorticoids and mineralocorticoids are associated with individual components of the MetS in women. (1) Tchernof et al.(2013), Physiol Rev, 93(1); (2) Constantinopoulos et al., (2015), Eur J Endocrinol, 172(1)